Association between Contact with Nature and Anxiety, Stress and Depression Symptoms: A Primary Survey in Brazil - Bressane, Adriano [UNESP]; Negri, Rogerio Galante [UNESP]; Brito Junior, Irineu de [UNESP]; Medeiros, Liliam Cesar de Castro [UNESP]; Araujo, Isabela Lopes Lima[UNESP]; Silva, Mirela Beatriz [UNESP]; Galvao, Amanda Louisi dos Santos [UNESP]; Rosa, Graziele Coraline Scofano da [UNESP] (Mdpi, 2022)
Mental health benefits have been linked to human interaction with nature. However, most studies have been carried out in developed countries, limiting the generalizability of empirical findings to other parts of the world. To address this gap, this study was conducted in Brazil. The objective of the study was to assess whether the frequency of contact with nature affects the occurrence of anxiety, stress, and depression. Data were collected between June and July 2022 through an online survey (n = 1186, 1 - alpha = 0.95, p = 0.05, 1 - beta = 0.85, rho = 0.1). Thus, the public online survey made it possible to carry out voluntary response sampling suitable for an exploratory study, with the purpose of an initial understanding of an under-researched population. First, a logistic regression was performed for quantifying the association between contact with nature and mental symptoms. In addition, three groups of people having different frequencies (low, medium, and high) of contact with nature and a reference group, comprised of those who reported no contact, were compared using Kruskal-Wallis and Dwass-Steel-Chritchlow-Fligner tests. This study employs a cross-sectional design and relies on retrospective recall. As a result, the research hypothesis was confirmed. People who very rarely have contact with nature had a 97.95% probability of moderate occurrence of stress, which decreases to 20.98% for people who have contact with nature frequently. Furthermore, in the same comparison, the probability of occurrence was 3.6 times lower for anxiety and 4.8 times lower for depression. In conclusion, the evidence indicates that the greater the frequency of contact with nature, the lower the occurrence of stress, anxiety, and depression symptoms. Nevertheless, the benefits of this contact were significant only when its frequency was moderate (about once or twice a week) or higher.
Keywords: Nature contact; Mental health; Primary survey; Brazil